A vítima no processo penal: Aspectos vitimológicos - Lima, Carlos Magno Moulin (2006)
The present study aims an analysis of the victim in to the brazilian s procedure system, examining it s historical bases, presenting diference with some south-american e europeans procedure systems. Not intending to enclose the subject, it will state that as important as the analysis related to the offense s sponsor, therefore the crime constitutes an violation to an item or an social life value, is the analysis of those who suffered the consequences of the criminal fact. Therefore, in addition to illustrate the importance of the victim s figure into the systems since the beginning of the civilization, it will take o the reader to the reflection about contemporary systems adopted by south American and European countries. It is important to mention that the procedure law haves non regular used measure by the offended to the damages repair caused by the delict, where upon it will report on assistance institutes and guarantee measure, still aplicated, with reserve, by the Law operators. It is an aim, either, demonstrate the offended position, since the moment of the arrestment of the suspect, going trough the police inquest instauration and the hypothesis of the criminal actions previewed by the actual procedure system. The subjects development will demonstrate the legislator s worry about the actual situation of the offended, not only with the procedure system, but also about the social context in with it is enrolled, analisating subjects as the damages repair, settlement and protection measure. Remain will to the reader the conviction that the brazilian procedure system, although far away from the evolutions suffered by the foreign systems, still predicts most important measure to the defense of the victim s rights e an to the equilibrium of Law and Democratic State